LEGAL PROTECTION OF THE CUSTOMARY RIGHTS OF THE RIMBA PEOPLE IN JAMBI PROVINCE - Irfan Hafiyyansah; I Nyoman Nurajaya; Herlindah (CV. RADJA PUBLIKA, 2025)
The state recognizes and protects Indigenous Law Communities (MHA) and their traditional rights in the constitution. One of the traditional rights held by MHA is customary rights. Some communities in Indonesia still live in groups and depend on the land/environment they recognize as customary rights. One of the Indigenous Law Communities is the Orang Rimba. The Orang Rimba live inside and outside forest areas, some of them still practice a semi-hunting-gathering culture and wander in the forest which they recognize as their living space. This study aims to examine the urgency of protecting the customary rights of the Orang Rimba and the implementation of the protection of their customary rights. Both issues are reviewed in normative juridical research, based on a set of regulations related to the recognition of MHA and customary rights that are still in effect in Indonesia. From the research conducted, it was found that the government has not fully provided legal protection for the customary rights of the Orang Rimba. The solution offered is a partnership agreement for area management and relocation of Orang Rimba settlements through the Remote Indigenous Community program.